Memorandum of understanding between Universiti Teknologi MARA and Universitas Amikom, Yogyakarta, Indonesia / Fakulti Filem, Teater dan Animasi - Universiti Teknologi MARA, Fakulti Filem, Teater dan Animasi (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on friendship, cooperation and collaboration.